Right to the Juke Joint : A Personal History of American Music - Mullen, Patrick B., 1941- (Book collections on Project MUSE., 2018)
"The cowboy songs and dusty Texas car rides of his youth set Patrick B. Mullen on a lifelong journey into the sprawling Arcadia of American music. That music fused so-called civilized elements with native forms to produce everything from Zydeco to Conjunto to jazz to Woody Guthrie. The civilized/native idea, meanwhile, helped develop Mullen's critical perspective, guide his love of music, and steer his life's work. Part scholar's musings and part fan's memoir, Right to the Juke Joint follows Mullen from his early embrace of country and folk to the full flowering of an idiosyncratic, omnivorous interest in music. Personal memory merges with a lifetime of fieldwork in folklore and anthropology to provide readers with a deeply informed analysis of American roots music. Mullen opens up on the world of ideas and his own tireless fandom to explore how his cultural identity--and ours--relates to concepts like authenticity and folkness. The result is a charming musical map drawn by a gifted storyteller whose boots have traveled a thousand tuneful roads."--Provided by publisher.